2017
DOI: 10.1016/j.redox.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

NOX isoforms in the development of abdominal aortic aneurysm

Abstract: Oxidative stress plays an important role in the formation of abdominal aortic aneurysm (AAA), and we have recently established a causal role of uncoupled eNOS in this severe human disease. We have also shown that activation of NADPH oxidase (NOX) lies upstream of uncoupled eNOS. Therefore, identification of the specific NOX isoforms that are required for eNOS uncoupling and AAA formation would ultimately lead to novel therapies for AAA. In the present study, we used the Ang II infused hph-1 mice to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(113 citation statements)
references
References 40 publications
(92 reference statements)
7
106
0
Order By: Relevance
“…It has been reported that deletion of p47 phox , which activates Nox1 and Nox2, prevents ANG II-induced AAA formation in apoEϪ/Ϫ mice (1048). Deletion of Nox1, Nox2, or Nox4 further diminished ANG II-dependent AAA and eNOS uncoupling in these mice (975). Systemic AMPK␣2 deficiency, but not bone marrow deficiency, in apoEϪ/Ϫ mice prevents ANG II-induced AAA development.…”
Section: Other Signal Intermediates Contributing To Aaamentioning
confidence: 92%
“…It has been reported that deletion of p47 phox , which activates Nox1 and Nox2, prevents ANG II-induced AAA formation in apoEϪ/Ϫ mice (1048). Deletion of Nox1, Nox2, or Nox4 further diminished ANG II-dependent AAA and eNOS uncoupling in these mice (975). Systemic AMPK␣2 deficiency, but not bone marrow deficiency, in apoEϪ/Ϫ mice prevents ANG II-induced AAA development.…”
Section: Other Signal Intermediates Contributing To Aaamentioning
confidence: 92%
“…Mechanistically, administration of a NOX4 inhibitor or siRNA abolished the homocysteine‐induced adventitial activation (Liu et al ., ). Moreover, NOX4 deficiency inhibited AAA formation‐induced by Ang II in mice with hyperphenylalaninaemia and uncoupled eNOS (Siu et al ., ). Thus, NOX4 mediates the adverse effects of homocysteine in adventitial inflammation and AAA formation (Liu et al ., ).…”
Section: The Mechanisms Of Vascular Injury Induced By Hhcymentioning
confidence: 97%
“…Myriad enzymes contribute to ROS generation, of which NOX family is dedicated generators of intracellular superoxide and hydrogen that strongly involve in redox signaling under healthy and pathological conditions [20][21][22]. NOX family consists of five isoforms including NOX1, NOX2, NOX3, NOX4 and NOX5, which accelerate ROS production in the vasculature [23][24][25][26][27].…”
Section: Nox Signalingmentioning
confidence: 99%